2018
DOI: 10.1002/epi4.12282
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies molecular diagnosis in children with drug‐resistant epilepsy

Abstract: Summary Objective Early onset drug‐resistant epilepsy is a neurologic disorder in which 2 antiepileptic drugs fail to maintain the seizure‐free status of the patient. Heterogeneous clinical presentations make the diagnosis challenging. We aim to identify the underlying genetic causes of a pediatric cohort with drug‐resistant epilepsy and evaluate whether the findings can provide information on patient management. Methods We include patients with drug‐resistant epilepsy onset before 18 years of age. Singleton c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 44 publications
(82 reference statements)
0
30
0
Order By: Relevance
“…Genetic Characteristics In Drug-resistant Epilepsy Of Published Studies Table 3 provides a summary of previous studies about genetic characteristics in DRE [12][13][14][15][16][17][18][19][20][21]. Regardless of varied molecular diagnostic tool used between studies, some gene mutations were found to appear repeatedly, such as SCN1A (5.6%, n = 74/1308), followed by SCN8A (1.37%, n = 18/1308), TSC2 (1.22%, n = 16/1308), SCN2A (1.07%, n = 14/1308) and KCNQ2 (0.99%, n = 13/1308) 3).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic Characteristics In Drug-resistant Epilepsy Of Published Studies Table 3 provides a summary of previous studies about genetic characteristics in DRE [12][13][14][15][16][17][18][19][20][21]. Regardless of varied molecular diagnostic tool used between studies, some gene mutations were found to appear repeatedly, such as SCN1A (5.6%, n = 74/1308), followed by SCN8A (1.37%, n = 18/1308), TSC2 (1.22%, n = 16/1308), SCN2A (1.07%, n = 14/1308) and KCNQ2 (0.99%, n = 13/1308) 3).…”
Section: Discussionmentioning
confidence: 99%
“…(7) For the subsequent 25 cases, WES was performed at the Department of Paediatric and Adolescent Medicine of HKU. (25) The exome library was prepared using the TruSeq Rapid Exome Library Prep Kit (Illumina) and sequenced using the Illumina NextSeq500 system. The in-house bioinformatics pipeline was used for data analysis.…”
Section: Whole-exome Sequencingmentioning
confidence: 99%
“…It is related to DS, also denominated as early childhood epileptic encephalopathy type 6. [11][12][13] In this disease, particularly, there are 12 possibilities of deleterious alterations observed, being 50% missense type (c.829T> C, c.971A> C, c.2360T> G, c.4093G> T, c.5178G> T and c .5434T> C), 25% splice sites (IVS2 + 1A> G, IVS4 + 1G> A and IVS8 + 3G> T), 17% frameshift type (c.3719_3720insGATA and c.1242delA), 8% deletion of a triplet (c.5489_5491delAGT). 14 Mutations provide a great risk of SUDEP, because this is a rare and severe progressive encephalopathy without concrete treatment.…”
Section: Scn1amentioning
confidence: 99%
“…14 Mutations provide a great risk of SUDEP, because this is a rare and severe progressive encephalopathy without concrete treatment. 13,14,29,37 Image 1 Cytogenetic location of SCNA1 gene: 2q24.3. Adapted from: Genetics Home Reference.…”
Section: Scn1amentioning
confidence: 99%
See 1 more Smart Citation